The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1101/2021.09.10.459871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic identification of viral sequences in laboratory reagents

Abstract: Metagenomic next–generation sequencing has transformed the discovery and diagnosis of infectious disease, with the power to characterize the complete infectome (bacteria, viruses, fungi, parasites) of an individual host organism. However, the identification of novel pathogens has been complicated by widespread microbial contamination in commonly used laboratory reagents. Using total RNA sequencing (metatranscriptomics) we documented the presence of contaminant viral sequences in multiple libraries of blank neg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Circoviridae and Genomoviridae contigs, as well as a complete pneumovirus genome detected in our sequencing libraries, were considered likely reagent‐associated contaminants (Porter et al., 2021) and not analyzed in this study. Notably, the majority of nr hits for circovirus sequences were to viruses from an environmental source, and a phylogenetic analysis of putative mammalian sequences revealed that all were likely reagent contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…Circoviridae and Genomoviridae contigs, as well as a complete pneumovirus genome detected in our sequencing libraries, were considered likely reagent‐associated contaminants (Porter et al., 2021) and not analyzed in this study. Notably, the majority of nr hits for circovirus sequences were to viruses from an environmental source, and a phylogenetic analysis of putative mammalian sequences revealed that all were likely reagent contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…Another probable contaminant was detected in the Miseq generated datasets, i.e., in the datasets of the healthy piglets and the piglets with signs of splay leg; reads and contigs classified as Equine infectious anemia. The common discovery of reads and contigs classified as Equine infectious anemia virus in datasets produced by metagenomic next-generation sequencing has recently been attributed to a reagent contaminant, a novel reagent-associated lenti-like virus [33]. Phylogenetic analysis of this novel reagent-associated lenti-like virus shows that it is closely related to and clusters with several known sequences of Equine infectious anemia virus, making it a recurrent classification and alignment error in datasets [33].…”
Section: Discussionmentioning
confidence: 99%
“…A few viral contigs were detected in all samples, but after blast validation almost all of them turned out to be from the Sus scrofa genome. One contig classified as Equine infectious anemia virus was detected in all samples and could be blast validated as Equine infectious anemia viru and thus most likely a reagent contaminant [33]…”
Section: Healthy Piglets (Miseq)mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, these viruses were removed from the bird libraries and excluded from all analyses. Additionally, any viruses that fell into the same clades as those found in blank libraries were conservatively assumed to be contaminants [46] and similarly removed. As a result of this screen one circo-like virus in Circoviridae (single-strand DNA viruses) was removed from the data set.…”
Section: Methodsmentioning
confidence: 99%